A hypervascular placental polyp after complete abortion: a case report - Ryan Spielvogel (BMC, 2023)
Abstract Background Placental polyps are rare complications of delivery or abortion. They are thought to complicate less than 0.25% of all pregnancies, although the actual incidence is unknown. While they typically occur within four weeks of delivery or abortion, they can have a variable presentation, which can lead to a delay in care. Case presentation A 35-year-old G4P2012 patient presented at 9 weeks gestation for a medication abortion. Post-abortion ultrasound after one week confirmed the abortion was complete and her bleeding ceased. The patient then presented two months later with the new onset of worrisome bleeding. She was found on ultrasound to have a new hypervascular polypoidal mass in the endometrial cavity. She then underwent an in-office dilation and curettage with an electric vacuum aspirator, which was curative. A follow up ultrasound three months later demonstrated no recurrence. Conclusions Placental polyps are a rare complication following pregnancy and should be included in the differential when a patient presents with bleeding and a new mass in the endometrial cavity on ultrasound following a delivery or abortion, even when frankly retained products of conception had been ruled out at time of abortion.